Kaolinite-based zeolites synthesis and their application in CO2 capture processes. (15th July 2022) - Cecilia, J.A.; Vilarrasa-García, E.; Morales-Ospino, R.; Finocchio, E.; Busca, G.; Sapag, K.; Villarroel-Rocha, J.; Bastos-Neto, M.; Azevedo, D.C.S.; Rodríguez-Castellón, E.
Highlights: Zeolite type A was synthesized from natural resources under mild conditions. Textural properties and crystallinity can be controlled through synthesis conditions. Microporosity plays a key role on CO2 /N2 and CO2 /H2 O selectivies. Under dry conditions, CO2 is readily desorbed at moderate temperatures. The presence of water hinders the desorption of the physisorbed species. Abstract: In light of the urgent need of reducing the atmospheric CO2 emissions, the use of low-cost adsorbents, that exhibit a high affinity and CO2 adsorption capacity, is a promising method from the economic and environmental point of view to separate CO2 from the flue gas emitted from large sources of emissions like power-fueled plants. Clay minerals are low-cost raw materials with high availability all over planet and great versatility in the fields of adsorption and catalysis processes. The present study pretends to elucidate the link between the reaction conditions during the synthesis of the zeolite from kaolinite and its CO2 adsorption capacity. For that purpose, the type A zeolite was synthesized via hydrothermal process in alkaline solution using metakaolinite as a starting material. The metakaolinite was obtained by calcination of kaolinite at 600 °C and some parameters such as temperature and synthesis time were modified to optimize the synthesis aiming for a high CO2 adsorption capacity adsorbent. Synthesized materials were characterized by X-ray diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), N2 adsorption–desorption at −196 °C and CO2 adsorption at 0 °C (up to 10 bars) isotherms and Nuclear Magnetic Resonance of solids (NMR). In addition, the adsorption capacity of CO2 was evaluated by means of CO2 adsorption–desorption isotherms at 25 °C up to atmospheric pressure. The obtained results indicated that synthesized zeolite 4A can be successfully prepared from natural kaolinite (via metakaolinization) at 100 °C for 48 h under alkaline conditions, showing chemical and physical properties similar to that of the commercial 4A zeolite.